MTS1338, A Small Mycobacterium tuberculosis RNA, Regulates Transcriptional Shifts Consistent With Bacterial Adaptation for Entering Into Dormancy and Survival Within Host Macrophages - Salina, Elena G.; Grigorov, Artem; Skvortsova, Yulia; Majorov, Konstantin; Bychenko, Oksana; Ostrik, Albina; Logunova, Nadezhda; Ignatov, Dmitriy; Kaprelyants, Arseny; Apt, Alexander; Azhikina, Tatyana (Frontiers in Cellular and Infection Microbiology, 2019)
Small non-coding RNAs play a significant role in bacterial adaptation to changing environmental conditions. We investigated the dynamics of expression of MTS1338, a small non-coding RNA of Mycobacterium tuberculosis, in the mouse model in vivo, regulation of its expression in the infected macrophages, and the consequences of its overexpression in bacterial cultures. Here we demonstrate that MTS1338 significantly contributes to host-pathogen interactions. Activation of the host immune system triggered NO-inducible up-regulation of MTS1338 in macrophage-engulfed mycobacteria. Constitutive overexpression of MTS1338 in cultured mycobacteria improved their survival in vitro under low pH conditions. MTS1338 up-regulation launched a spectrum of shifts in the transcriptome profile similar to those reported for M. tuberculosis adaptation to hostile intra-macrophage environment. Using the RNA-seq approach, we demonstrate that gene expression changes accompanying MTS1338 overexpression indicate reduction in translational activity and bacterial growth. These changes indicate mycobacteria entering the dormant state. Taken together, our results suggest a direct involvement of this sRNA in the interplay between mycobacteria and the host immune system during infectious process.